Project-Based Learning Model in Learning to Write Explanation Text for Vocational High School - Cahyono, Bambang Eko Hari; Widyaningrum, Heny Kusuma; Pratiwi, Cerianing Putri (Qalamuna (online), 2024)
The purpose of this study is to describe and explain the ability to write explanatory texts of vocational school students, the implementation of the project-based learning (PjBL) model in improving the ability to write explanatory texts, and the strengths and weaknesses faced by teachers and students in implementing the project-based learning model. This research is crucial for enhancing the quality of writing instruction in vocational high schools. The research approach uses a qualitative descriptive approach. The subjects of this research were vocational high school students in Madiun. Data collection techniques were carried out through documentation, passive role observation, and) in-depth interviews. Data analysis was done using an interactive analysis model, carried out through 3 activity flows: data reduction, data presentation, and conclusion. This study revealed various problems in learning to write explanatory texts in vocational high schools. The results of the research show that: (1) students' ability to write explanatory texts is not by the structure of explanatory texts; (2) the direct impact of implementing the PjBL model is increasing students' ability to write explanatory texts; (3) the advantage of this model is that it provides experience for students that emphasizes practice in completing assignments and projects according to real-world conditions, while the disadvantages are that it requires the skills and activity of teachers and students, and quite time consuming especially in completing the project.